Perancangan primer gen lktB pada Fusobacterium necrophorum untuk analisis PCR - Rian Ka Praja; Reny Rosalina (Universitas Sulawesi Barat, 2021)
Fusobacterium necrophorum is a pathogen causing disease in animals, especially cattle, goats, and sheep. F. necrophorum infection can result in a variety of necrotic conditions (necrobacillosis). This study aimed to design a pair of primers for detecting the leukotoxin B (lktB) gene expressed by F. necrophorum as diagnostic support. The lktB gene sequence was obtained from GenBank NCBI with accession number AF312861.3:685-2337. Furthermore, the sequence was used as a template for in silico primer design using Primer-BLAST. Primer candidates successfully designed were then analyzed for their secondary structure using NetPrimer. The results showed that forward primer set 6 (5'-TCGGATGCTGGAATGCTACTT-3') and reverse primer set 6 (5'-GGGCTCCCAAATCCTTACGA-3') were a favorable primer set with a product size of 228 bp. However, laboratory experiments need to be carried out to determine the optimal conditions for this primer set.